ISOLASI BAKTERI MICROBIAL FUEL CELL PADA LIMBAH CAIR TAHU SEBAGAI SUMBER ENERGI LISTRIK UNTUK PENGAYAAN MODUL MIKROBIOLOGI DASAR - Irda Sayuti; Imam Mahadi; M. Irsyad Nur (Biogenesis, 2017)
ABSTRACT This research was to determine the genus of bacteria can produce electricity energy used microbial fuel cell series in waste water of tofu and develop module in enviromental mikrobiology concept in basic microbiology among December 2015- May 2016. This research did by 2 phases : isolate microbial fuel cell bakteria in waste water of tofu and development of the module. This research is descriptive, sampling did by purposive sampling, with pick sample in 3 spot there are 2 m,4 m dan 6 m in river bank from source discharges,with considering the existence of tofu waste clumps in the river source waste disposal. Parameter in this research there are test electrical energy, isolate bacteria of microbial fuel cell, and develop the module of basic microbiology. The highest electricity energy in this research observed on the 40th hour of 67,2 mV,kind of bacteria in microbial fuel cell series in tofu waste water are Entrobacter,Desulfomaculum,Sulfobacterium. Result of this research beused for unit module in enviroment microbiology concept in basic microbiology course.  Key words: Microbial Fuel Cell bacteria, tofu waste water,electricity energy, module